Proving The Existence and the Uniqueness Solutions of fractional Integro- Differential Equations - Al-Fayadh, Seema’a (Iraqi Journal of Science, 2024)
In this paper, we will study and prove the existence and the uniqueness theoremsof solutions of the generalized linear integro-differential equations with unequalfractional order of differentiation and integration by using Schauder fixed pointtheorem. This type of fractional integro-differential equation may be considered as ageneralization to the other types of fractional integro-differential equationsConsidered by other researchers, as well as, to the usual integro-differentialequations.